The Correlation between Students' Grammar Mastery and Their Reading Comprehension Ability during Online Class - Afina Fika Rahma (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The aim of this research was to find out the relationship between grammar mastery, and reading comprehension ability. The sample consisted of 29 EFL students in the third semester of English Department at the University of Islam Malang and the instrument were scores of grammar mastery and reading comprehension ability. The collected data were analyzed by Pearson Product Moment Correlation by applying IBM SPSS 20.0. The research findings showed a significant positive correlation between grammar mastery and reading comprehension ability because the significance demonstrated on the table was 0.000<0.05 level of significance. Then, the coefficient correlation obtained shown on the table was 0.631. It was indicated that grammar mastery was significantly correlated with reading comprehension ability. Therefore, it was concluded that the students’ grammar mastery contributed significantly to their reading comprehension ability. Based on the finding, it can be suggested that students should involve grammar when reading to get the message conveyed by the author. Besides that, the role of the lecturer is also essential to motivate students so that they can improve their grammar background knowledge.